Do schools reinforce or reduce learning gaps between advantaged and disadvantaged students? Evidence from Vietnam and Peru - Glewwe, P; Krutikova, S; Rolleston, C (Young Lives, 2014)
This paper examines whether disadvantaged children learn less than advantaged children when both types of children are enrolled in the same school for two developing countries, Vietnam and Peru. This is done by estimating education production functions that contain two school fixed effects for each school, one for advantaged children and one for disadvantaged children. The paper examines six different definitions of disadvantage, based on household wealth, having low cognitive skills at age 5, gender, ethnic minority group (Peru only), maternal education, and nutritional status. The results show no sign of discrimination against disadvantaged groups in Vietnam; indeed if anything one advantaged group, males, seems to do worse in school than the corresponding disadvantaged group, females. In contrast, in Peru ethnic minority students and students who enter primary school with low cognitive skills appear to learn less in school than ethnic majority students and students with relatively high cognitive skills who are enrolled in the same school, respectively.